IMPLEMENTASI NILAI-NILAI MODERASI BERAGAMA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA NEGERI 6 MUARO JAMBI - Ariska Miftaharo, Weni; Fadhil, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of religious moderation values in Islamic Religious Education (PAI) at SMP Negeri 6 Muaro Jambi and to identify its supporting and inhibiting factors. The research employs a qualitative approach with a case study design, involving PAI teachers, the school principal, and students as informants through observations, in-depth interviews, and documentation. The results indicate that religious moderation values have been integrated into learning materials, teaching methods, teacher role modeling, and extracurricular activities, with an average achievement of 86% (very good category). The main supporting factors include school leadership policies, the Merdeka Curriculum, student participation, and adequate facilities, while the inhibiting factors include social environment influences, limited specialized literature, differences in teacher understanding, and limited instructional time. The study demonstrates that the implementation of religious moderation at SMP Negeri 6 Muaro Jambi has been effective but still requires reinforcement of literature, teacher training, and community collaboration to ensure the values of moderation are optimally internalized.